As histórias em quadrinhos como materiais linguísticos no livro didático de Língua Portuguesa do 9° ano do ensino fundamental - MIRANDA, Ana Cristina Cardoso (2023)
This paper addresses the genre Stories in Comics (comics) and how it is exercised their role in teaching of Portuguese in the last year of basic education in their activities applicative. This study is to analyze the comic books in Portuguese Language Textbook considering its usefulness in the activity of understanding, interpretation and production of texts for the purpose of exercising the reasoning and creative imagination of the student in their prospects for learning and not as mere illustration without no function. The Textbook (LDs) Portuguese Language (LP) in 9th grade have several activities for the teaching and learning of the mother tongue of the student as a way to provide them with effective learning and remunerative. Because of this, is that many types of genres have been proposed to textbooks, to meet a reading of interpretation considering the student's knowledge in their day to day and place in which he is involved.